The Effect of Acute Citrulline Malate Supplementation on Mitochondrial Function, Oxygen Saturation, Handgrip Critical Force, and Recovery of Force in the Forearm Muscles. - Hodges, Elise (My University, 2023)
Citrulline Malate has possible exercise performance enhancement abilities due to the vasodilatory effect of nitric oxide produced from citrulline combined with a possible increase in mitochondrial efficiency from malate. However, the latter mechanism is unclear and has not been studied in conjunction with an aerobic performance test. Additionally, there has been a lack of studying how a large enough dose with proper pharmacokinetic timing from consumption to exercise affects these measures. PURPOSE: The purpose of this study was to investigate how an acute, 12g dose of citrulline malate affects mitochondrial function, oxygen saturation, and performance of a handgrip critical force test in the forearm muscles. METHODS: Seventeen participants (all women aged 18-35 years) completed three visits consisting of one familiarization and two experimental. This study utilized a randomized, double-blind, crossover design where participants drank either a citrulline malate or placebo solution, underwent a one-hour rest period, completed the mitochondrial function test, and then performed the handgrip critical force test followed by four recovery contractions. Mitochondrial function (time constant tau values), oxygen saturation and desaturation during the handgrip test (measured using infrared spectroscopy), and critical force variables were measured and compared between the supplement and placebo days. RESULTS: No statistical differences for mitochondrial function, maximal strength, critical force, force-time integral, areas-under the curve for oxy- and deoxy-hemoglobin, hemoglobin difference, and tissue saturation index were found. Additionally, there was no significant difference between the rate of recovery of force (p > 0.05). While there were no significant differences between conditions for the 20-second, time-binned averages of oxy/deoxy-hemoglobin, hemoglobin difference, and tissue saturation index during the handgrip critical force test (p > 0.05), there were significant main effects for time for all four of these variables (p < 0.001). CONCLUSIONS: In conclusion, an acute, 12g dose of citrulline malate had no influence on mitochondrial function, oxygen saturation or desaturation, or performance of a handgrip critical force test. Future studies should investigate other mechanisms involved with this supplement, how or if citrulline malate affects electrically stimulated critical torque, or how other nitric oxide-producing supplements (like beet-root juice) affect mitochondrial function or aerobic performance. A larger sample size should also be included in future studies.
Keywords: critical force; mitochondrial function; citrulline malate supplementation; recovery of force